Route Fidelity during Marine Megafauna Migration - Horton, Travis W.; Hauser, Nan; Zerbini, Alexandre N.; Francis, Malcolm P.; Domeier, Michael L.; Andriolo, Artur; Costa, Daniel P.; Robinson, Patrick W.; Duffy, Clinton A. J.; Nasby-Lucas, Nicole; Holdaway, Richard N.; Clapham, Phillip J. (Frontiers in Marine Science, 2017)
The conservation and protection of marine megafauna require robust knowledge of where and when animals are located. Yet, our ability to predict animal distributions in space and time remains limited due to difficulties associated with studying elusive animals with large home ranges. The widespread deployment of satellite telemetry technology creates unprecedented opportunities to remotely monitor animal movements and to analyse the spatial and temporal trajectories of these movements from a variety of geophysical perspectives. Reproducible patterns in movement trajectories can help elucidate the potential mechanisms by which marine megafauna navigate across vast expanses of open-ocean. Here, we present an empirical analysis of humpback whale (Megaptera novaeangliae), great white shark (Carcharodon carcharias) and northern elephant seal (Mirounga angustirostris) satellite telemetry-derived route fidelity movements in magnetic and gravitational coordinates. Our analyses demonstrate that: 1) humpback whales, great white sharks and northern elephant seals are capable of performing route fidelity movements across millions of square kilometers of open ocean with a spatial accuracy of better than 150 km despite temporal separations as long as 7 years between individual movements; 2) route fidelity movements include significant (p<0.05) periodicities that are comparable in duration to the lunar cycles and semi-cycles; 3) latitude and bedrock-dependent gravitational cues are stronger predictors of route fidelity movements than spherical magnetic coordinate cues when analysed with respect to the temporally dependent moon illumination cycle. We further show that both route fidelity and non-route fidelity movement trajectories, for all three species, describe overlapping in-phase or antiphase sinusoids when individual movements are normalised to the gravitational acceleration present at migratory departure sites. Although these empirical results provide an inductive basis for the development of testable hypotheses and future research questions, they cannot be taken as evidence for causal relations between marine megafauna movement decisions and geophysical cues. Experiments on model organisms with known sensitivities to gravity and magnetism, complemented by further empirical observation of free-ranging animals, are required to fully explore how animals use discrete, or potentially integrated, geophysical cues for orientation and navigation purposes.